Preparation method and application of organic battery composite positive electrode

CN117096304BActive Publication Date: 2026-10-27TIANJIN UNIV
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202311052881.7
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-08-21
Publication Date
2026-10-27
Estimated Expiration
2043-08-21

AI Technical Summary

Technical Problem

[0007]本发明旨在解决导电聚合物的容量低以及目前已有技术中高掺杂水平与循环稳定性的矛盾、操作复杂以及成本高等问题

Benefits of technology

[0022]本发明具有的特点和优势:操作简单、原料价格低廉且来源广泛、绿色环保、可实现大规模生产,满足实际应用的第一要求;苯胺为液体,无法实现固态聚合,1-氨基萘活性位点密度低,无法实现更高的比容量和能量密度,1,8-二氨基萘具有高的活性位点密度,具有更高的理论比容量;聚合物的制备方法基本为传统的化学氧化法,但这种方法制备的聚合物在电极制备过程中极易团聚,导致差的电化学性能;原位电化学聚合可以在一定程度上改善电极结构的形貌,但仍有大块的聚合物颗粒;我们通过将1,8-二氨基萘封装到活性碳的纳米孔内制备成1,8-二氨基萘/活性碳纳米复合物材料,并制备电极,在充电过程中单体在纳米孔内原位聚合,进而形成纳米结构的多孔电极,改善电极结构的形貌,提高聚合物的掺杂水平,纳米孔也可以为形成的聚合物链在充放电过程中的体积变化提供充足的缓冲空间,延长电极的循环寿命;在半电池测试中,制备的1,8-二氨基萘/活性碳纳米复合物正极材料具有高达373.4mAhg-1的可逆比容量(目前聚1,8-二氨基萘正极材料的容量仅为171mAh g-1),在高达60A g-1的电流密度下其比容量仍能够保持在266.7mAh g-1,同时,原位电聚合形成难溶解的聚合物,使其具有良好的循环稳定性,在20A g-1的电流密度下,0.3-1.8V电压范围内,1,8-二氨基萘/活性碳纳米复合物正极材料具有50000圈的长循环寿命。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN117096304B_ABST
    Figure CN117096304B_ABST
Patent Text Reader

Abstract

The application relates to a preparation method and application of an organic battery composite positive electrode, a monomer / porous carbon nanocomposite material prepared by an evaporation method with 1,8-diaminonaphthalene as a monomer and porous carbon as a carrier; the prepared monomer / porous carbon nanocomposite material is prepared into an electrode, and a battery is assembled; after the monomer is in-situ electropolymerized in the battery during charging of the battery, an organic battery-electrolyte integrated composite material is formed with an electrolyte. The monomer and the porous carbon are prepared into a nanocomposite material for the first time, the prepared 1,8-diaminonaphthalene / activated carbon nanocomposite positive electrode material has a reversible specific capacity as high as 373.4 mAh g ‑1 , the specific capacity can still be maintained at 266.7 mAh g ‑1 under a current density as high as 60 A g ‑1 , and the 1,8-diaminonaphthalene / activated carbon nanocomposite positive electrode material has a long cycle life of 50000 times. The method is simple in operation and can be used for large-scale production.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to a method for preparing and applying an organic battery composite cathode, belonging to the field of electrochemical energy storage technology. Background Technology

[0002] Aqueous rechargeable zinc-ion batteries have attracted widespread attention due to their low cost and high safety. However, traditional zinc-ion batteries mostly use layered oxides, polyanions, and Prussian blue as cathode materials, but their limited resources, environmental unfriendliness, and high toxicity restrict their development. Furthermore, they store energy by inserting / extracting zinc ions, which largely depends on the crystal structure of the inorganic cathode, but this structure is often unstable during cycling, leading to poor cycle performance. Therefore, polymer electrode materials, with their structural diversity and designability, abundant raw materials, and environmental friendliness, show great promise for application.

[0003] While polymer electrode materials offer numerous advantages, they still face challenges related to electrode structure and low conductivity. In-situ electrochemical polymerization involves preparing electrodes from small molecules carrying electrochemically polymerizable active groups. During battery charging, these small molecules polymerize in situ within the battery, forming a polymer that significantly improves the electrode structure. However, polymers prepared using traditional chemical oxidation methods are prone to aggregation during electrode fabrication due to strong intermolecular forces, leading to poor battery kinetic performance and low utilization of active sites. In 2022, Wang et al. prepared a poly(1,8-diaminonaphthalene) electrode using a traditional oxidation method at 0.1 Ag... -1 It only exhibits 171 mAh g at current density -1 The initial discharge capacity corresponds to an active site utilization rate of only about 50%.

[0004] Therefore, it is crucial to explore novel organic-organic composite cathode materials with good distribution structure, improved electronic conductivity, and high safety.

[0005] This patent is the first to prepare a nanocomposite material from 1,8-diaminonaphthalene and porous carbon. Utilizing in-situ electropolymerization and the nano-confinement effect of the nanopores, the monomers are in-situ polymerized within the porous carbon to form a nanostructured polymer porous electrode. This significantly improves the utilization rate of the polymer's active sites, and the resulting electrode exhibits excellent cycle stability. This invention effectively fills the gap in the preparation of organic battery composite materials using in-situ electrochemical polymerization. Summary of the Invention

[0006] This invention addresses the problems of existing technologies by, for the first time, preparing a nanocomposite material from monomers and porous carbon. Utilizing in-situ electropolymerization and the nano-confinement effect of the nanopores, a novel organic battery composite cathode material is prepared. This significantly improves the utilization rate of the active sites of the conductive polymer while exhibiting excellent kinetic performance and cycle stability. This invention effectively fills a gap in the field of organic battery composite cathodes, their preparation methods, and applications.

[0007] The present invention aims to solve the problems of low capacity of conductive polymers and the contradiction between high doping level and cycle stability, complex operation and high cost in existing technologies.

[0008] This invention uses porous carbon as a carrier for preparing conductive polymers. A monomer / porous carbon nanocomposite material is prepared by a simple evaporation method. After in-situ electropolymerization, it forms an organic battery composite cathode material with an electrolyte.

[0009] The technical solution of the present invention is as follows:

[0010] A method for preparing an organic battery composite cathode material includes the following steps:

[0011] 1) Monomer / porous carbon nanocomposite material prepared by evaporation method using 1,8-diaminonaphthalene as monomer and porous carbon as carrier;

[0012] 2) The prepared monomer / porous carbon nanocomposite material is used to prepare electrodes and assemble batteries. During battery charging, the monomer undergoes in-situ electropolymerization inside the battery and then forms an organic battery-electrolyte integrated composite material with the electrolyte.

[0013] Step 1) involves dissolving the monomer in dichloromethane, trichloromethane, or dimethyl sulfoxide to form a monomer organic solution, adding porous carbon to the solution, sonicating the mixture until homogeneous, and then drying it under vacuum at room temperature to 100°C until completely dry, thus obtaining the monomer / porous carbon nanocomposite material.

[0014] The preferred concentration of the monomeric organic solution is 2-6 mg / ml.

[0015] The preferred mass ratio of monomer to porous carbon is 2:1-6.

[0016] The present invention prepares a composite cathode material for use in battery cathodes.

[0017]

[0018] The preparation method in step (2) adopts a conventional electrode preparation method, including the following steps:

[0019] (1) The prepared monomer / porous carbon nanocomposite material, carbon black and polyvinylidene fluoride or sodium alginate are dispersed in N-methylpyrrolidone or water at a mass ratio of 60-80:30-10:10. After the slurry is stirred evenly, it is coated on aluminum foil. After drying at 50-70℃ for 2-6 hours, it is cut into electrode sheets and used as the positive electrode. The battery adopts a 2032 coin cell, with glass fiber as the separator, zinc foil as the negative electrode, and 3M Zn(OTf)2in Water as the electrolyte.

[0020] (2) After assembling the battery, it was placed in the Land 2001A battery testing system for electrochemical performance testing. The test voltage range was 0.3-1.8V. During the first charge cycle, under the action of the electric field, the monomers were electropolymerized in situ in the nanopores to form a conductive polymer electrode with a nanostructure.

[0021] The effects of this invention are explained as follows:

[0022] The features and advantages of this invention are: simple operation, low and widely available raw materials, environmentally friendly, and capable of large-scale production, meeting the primary requirements of practical applications; aniline is a liquid and cannot be polymerized in a solid state, and 1-aminonaphthalene has a low active site density, making it impossible to achieve higher specific capacity and energy density, while 1,8-diaminonaphthalene has a high active site density and a higher theoretical specific capacity; the polymer preparation method is basically the traditional chemical oxidation method, but the polymer prepared by this method is prone to agglomeration during electrode preparation, resulting in poor electrochemical performance; in-situ electrochemical polymerization can improve the morphology of the electrode structure to a certain extent. However, large polymer particles still remained. We prepared a 1,8-diaminonaphthalene / activated carbon nanocomposite material by encapsulating 1,8-diaminonaphthalene within the nanopores of activated carbon, and then fabricated an electrode. During charging, the monomers polymerized in situ within the nanopores, forming a porous electrode with a nanostructure. This improved the electrode morphology and increased the polymer doping level. The nanopores also provided sufficient buffer space for the volume changes of the polymer chains during charging and discharging, extending the electrode's cycle life. In half-cell testing, the prepared 1,8-diaminonaphthalene / activated carbon nanocomposite cathode material exhibited a high capacity of 373.4 mAh g / g. -1 The reversible specific capacity (currently, the capacity of poly(1,8-diaminonaphthalene) cathode material is only 171 mAh g) -1 ), at a maximum of 60A g -1 Its specific capacity can still be maintained at 266.7 mAh g at a current density. -1 Simultaneously, in-situ electropolymerization forms a poorly soluble polymer, giving it good cycling stability at 20 A g. -1 At a current density of 0.3-1.8V, the 1,8-diaminonaphthalene / activated carbon nanocomposite cathode material exhibits a long cycle life of 50,000 cycles.

[0023] This method encapsulates the polymerizable monomer 1,8-diaminonaphthalene into the nanopores of activated carbon via a simple evaporation process, constructing a monomer / porous carbon nanocomposite material and preparing an electrode. During charging, the monomer undergoes in-situ electropolymerization within the nanopores to form a conductive polymer cathode composite material with a nanostructure. This method is simple to operate, uses inexpensive and readily available raw materials, and can be used for large-scale production. Attached Figure Description

[0024] Figure 1 The nitrogen adsorption-desorption curve (a), pore size distribution curve (b), XRD curve (c), scanning electron microscope (SEM) images (d, e) of the activated carbon, and SEM images (f, g) of the 1,8-diaminonaphthalene / activated carbon nanocomposite material prepared in Example 3 are shown.

[0025] Figure 2 The charge-discharge curves of the 1,8-diaminonaphthalene / activated carbon nanocomposite material cathode were measured in Example 8.

[0026] Figure 3 The long-cycle stability of the 1,8-diaminonaphthalene / activated carbon nanocomposite material cathode was measured in Example 8.

[0027] Figure 4 The rate performance of the 1,8-diaminonaphthalene / activated carbon nanocomposite material cathode was measured in Example 8. Detailed Implementation

[0028] To make the objectives, technical solutions, and advantages of this invention clearer, the invention will be further described below in conjunction with specific embodiments.

[0029] Example 1 - Preparation of 1,8-diaminonaphthalene / activated carbon nanocomposite materials

[0030] The 1,8-diaminonaphthalene / activated carbon nanocomposite material was prepared by evaporation. 30 mg of 1,8-diaminonaphthalene was dissolved in 15 ml of chloroform (2 mg / ml), and 15 mg of activated carbon was added. After sonicating the mixed solution for 1.5 hours, it was vacuum dried at 50 °C for 6 hours to obtain the 1,8-diaminonaphthalene / activated carbon nanocomposite material.

[0031] Example 2 - Preparation of 1,8-diaminonaphthalene / activated carbon nanocomposite material

[0032] The 1,8-diaminonaphthalene / activated carbon nanocomposite material was prepared by evaporation. 30 mg of 1,8-diaminonaphthalene was dissolved in 15 ml of chloroform (2 mg / ml), and 30 mg of activated carbon was added. After sonicating the mixed solution for 1.5 hours, it was vacuum dried at 50 °C for 6 hours to obtain the 1,8-diaminonaphthalene / activated carbon nanocomposite material.

[0033] Example 3 - Preparation of 1,8-diaminonaphthalene / activated carbon nanocomposite material

[0034] The 1,8-diaminonaphthalene / activated carbon nanocomposite material was prepared by evaporation. 30 mg of 1,8-diaminonaphthalene was dissolved in 7.5 ml of dichloromethane (4 mg / ml), and 60 mg of activated carbon was added. After sonicating the mixed solution for 1 hour, it was vacuum dried at room temperature for 5 hours to obtain the 1,8-diaminonaphthalene / activated carbon nanocomposite material.

[0035] The test results of Example 3 are analyzed and discussed below. (Appendix) Figure 1 The nitrogen adsorption-desorption curve (a), pore size distribution curve (b), XRD curve (c), and scanning electron microscope (SEM) images (d, e) of the activated carbon and (f, g) of the 1,8-diaminonaphthalene / activated carbon nanocomposite material are listed. From the nitrogen adsorption-desorption curve and pore size distribution curve of the 1,8-diaminonaphthalene / activated carbon nanocomposite material, it can be clearly observed that after encapsulating the monomeric 1,8-diaminonaphthalene into activated carbon, the specific surface area increased from 2710.7 m² / s. 2 g -1 Reduced to 1035.0m 2 g -1 The pore volume is 1.42cm 3 g -1 Reduced to 0.55cm 3 g -1 This indicates that the monomer has entered the nanopores of the activated carbon. In XRD testing, almost no diffraction peaks of the monomer 1,8-diaminonaphthalene were observed in the 1,8-diaminonaphthalene / activated carbon nanocomposite material, and in SEM characterization of the 1,8-diaminonaphthalene / activated carbon nanocomposite material, no 1,8-diaminonaphthalene was observed outside the activated carbon. These results further indicate that the monomer 1,8-diaminonaphthalene has completely entered the nanopores of the activated carbon.

[0036] Example 4 - Preparation of 1,8-diaminonaphthalene / activated carbon nanocomposite material

[0037] The 1,8-diaminonaphthalene / activated carbon nanocomposite material was prepared by evaporation. 30 mg of 1,8-diaminonaphthalene was dissolved in 5 ml of dimethyl sulfoxide (6 mg / ml), and 90 mg of activated carbon was added. After sonicating the mixed solution for 3 hours, it was vacuum dried at 100 °C for 8 hours to obtain the 1,8-diaminonaphthalene / activated carbon nanocomposite material.

[0038] Example 5 - Preparation of 1,8-diaminonaphthalene / activated carbon nanocomposite electrode material

[0039] The 1,8-diaminonaphthalene / activated carbon nanocomposite material prepared in Examples 1-4, carbon black, and polyvinylidene fluoride (sodium alginate) were dispersed in 5 ml of N-methylpyrrolidone (water) at a mass ratio of 60:30:10. After the slurry was stirred evenly, it was coated on aluminum foil with a thickness controlled at 20 μm. It was dried at 50-70℃ for 6 hours and rolled into an electrode sheet with a diameter of 9 mm using a cutter. Then it was transferred to a glove box for later use.

[0040] Example 6 - Preparation of 1,8-diaminonaphthalene / activated carbon nanocomposite electrode material

[0041] The 1,8-diaminonaphthalene / activated carbon nanocomposite material prepared in Examples 1-4, carbon black and polyvinylidene fluoride (sodium alginate) were dispersed in 5 ml of N-methylpyrrolidone (water) at a mass ratio of 70:20:10. After the slurry was stirred evenly, it was coated on aluminum foil with a thickness controlled at 20 μm. It was dried at 50-70℃ for 6 hours and rolled into an electrode sheet with a diameter of 9 mm using a cutter.

[0042] Example 7 - Preparation of 1,8-diaminonaphthalene / activated carbon nanocomposite electrode material

[0043] The 1,8-diaminonaphthalene / activated carbon nanocomposite material prepared in Examples 1-4, carbon black and polyvinylidene fluoride (sodium alginate) were dispersed in 5 ml of N-methylpyrrolidone (water) at a mass ratio of 80:10:10. After the slurry was stirred evenly, it was coated on aluminum foil with a thickness controlled at 20 μm. It was dried at 50-70℃ for 6 hours and then rolled into an electrode sheet with a diameter of 9 mm using a cutter.

[0044] Example 8 - Battery Assembly and Testing Conditions

[0045] Battery assembly was performed in air. The battery used was a 2032 coin cell with glass fiber as the separator. The electrode prepared in Example 7 was used as the positive electrode, and zinc foil as the negative electrode. The electrolyte was 3M Zn(OTf)2in Water. After assembly, the battery was placed in a Land 2001A battery testing system for electrochemical performance testing. The test voltage range was 0.3-1.8V, and the test current density was 0.2A g. -1 and 20A g-1 The rate performance test current density is 0.2A g. -1 Gradually increase to 60A g -1 .

[0046] The test results of Example 8 are analyzed and discussed below. (Appendix) Figure 2 The following are listed: 1,8-diaminonaphthalene / activated carbon nanocomposite material electrode (1,8-diaminonaphthalene: activated carbon = 30 mg: 60 mg, 1,8-diaminonaphthalene / activated carbon nanocomposite material: carbon black: polyvinylidene fluoride = 80: 10: 10) at 0.2 A g. -1 Charge and discharge curves (with attached) Figure 2 ), 20A g -1 Long-term cycling stability at current density (with appendix) Figure 3 ) and the rate performance of the 1,8-diaminonaphthalene / activated carbon nanocomposite electrode (attached) Figure 4 The charge-discharge curves show that the 1,8-diaminonaphthalene / activated carbon nanocomposite electrode exhibits high performance at 0.2 A g. -1 At a current density, its first-cycle discharge specific capacity reaches as high as 373.4 mAh g. -1 In long-cycle performance testing, the prepared 1,8-diaminonaphthalene / activated carbon nanocomposite cathode material showed good performance at 20 A g. -1 It exhibits a cycle life of up to 50,000 cycles at current densities; in rate performance testing, the electrode achieves a rate performance of up to 60 A g. -1 With its ultrafast rate performance, this electrode far surpasses most reported cathode materials in terms of discharge specific capacity, cycle life, and rate performance.

[0047] Those skilled in the art should understand that this invention is not limited to the above embodiments, which are preferred embodiments of the invention. Various changes and modifications can be made to the invention without departing from its spirit and scope, and all such changes and modifications fall within the scope of the invention as claimed. The scope of protection of this invention is defined by the appended claims and their equivalents.

Claims

1. The application of a 1,8-diaminonaphthalene / activated carbon nanocomposite cathode material in battery cathodes, characterized in that, Includes the following steps: 1) Using 1,8-diaminonaphthalene as a monomer and porous carbon as a support, monomer / porous carbon nanocomposite materials were prepared by evaporation. 2) The prepared monomer / porous carbon nanocomposite material is used to prepare an electrode. The electrode is used as the positive electrode and the zinc foil is used as the negative electrode. The electrolyte is Zn(OTf)2 aqueous solution to assemble the battery. During battery charging, the monomer is electropolymerized in situ inside the battery and then forms an organic battery-electrolyte integrated composite material with the electrolyte. Step 1) involves dissolving the monomer in dichloromethane, trichloromethane, or dimethyl sulfoxide to form a monomer organic solution, adding porous carbon to it, sonicating the mixture until homogeneous, and then drying it under vacuum at room temperature to 100°C until completely dry to obtain the monomer / porous carbon nanocomposite material.

2. The application as described in claim 1, characterized in that, The concentration of the monomeric organic solution is 2-6 mg / ml.

3. The application as described in claim 1, characterized in that, The mass ratio of monomer to porous carbon is 2:1-6.

Citation Information

Patent Citations

  • Preparation method of conductive polymer positive electrode material with high doping availability

    CN115275192A